DETRIMENTAL IMPACT OF CRYOPRESERVATION ON BUFFALO BULL SPERM MOTILITY, VIABILITY AND MEMBRANE INTEGRITY DUE TO EFFLUX OF MEMBRANE CHOLESTEROL - SINGH, N; CHEEMA, RS; KUMAR, A; KAUR, M; DHALIWAL, GS (The Indian Journal of Animal Reproduction, 2016)
Thirty ejaculates from six buffalo bulls were used in the present study. Subsequent to cryopreservation, cholesterol content of buffalo bull sperms was reduced as compared to pre-freeze stage (p
Keywords: Buffalo bull; Cholesterol; Cryopreservation; Sperm; Semen